2009
DOI: 10.1097/pcc.0b013e3181956b76
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of two approaches to parenteral nutrition in critically ill children*

Abstract: Parenteral nutrition with standard solutions offers the potential of a relevant cost reduction compared with individualized admixtures in critically ill children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…Their energy expenditures are not only related to the maintenance of body tissue but also to additional needs for growth and development. 1,2 Special guidelines have been developed to address the needs of parenteral nourished neonates and children. 1 In general, two mechanisms to deliver PN are available: standard PN solutions, or individualized admixtures compounded in hospital or by external suppliers.…”
Section: Introductionmentioning
confidence: 99%
“…Their energy expenditures are not only related to the maintenance of body tissue but also to additional needs for growth and development. 1,2 Special guidelines have been developed to address the needs of parenteral nourished neonates and children. 1 In general, two mechanisms to deliver PN are available: standard PN solutions, or individualized admixtures compounded in hospital or by external suppliers.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that the direct cost for manufacturing standard solutions were similar or reduced, when compared to individualised PN. Gamsjaeger et al [30] compared the actual cost of individualised PN versus standard PN and found that, on average, individualised PN per day cost 82.78 Euros, versus 61.21 Euros. In our unit, there were concerns related to the wastage of volume in standard PN.…”
Section: Discussionmentioning
confidence: 99%
“…Bei kurzfristiger totaler und partieller PE bietet sich die Verwendung von Standardlösungen an [276]. Hierdurch kann auch eine Kostenreduktion erreicht werden [277]. Eine retrospektive Studie mit Frühgeborenen verglich eine Standard-PE mit einer verhältnismäßig höheren Zufuhr an Aminosäuren, Glukose und einem besseren Kalzium-Phosphat-Verhält-nis mit einer individualisierten PE.…”
Section: Sind Standardlösungen Für Pädiatrische Patienten Von Nutzen?unclassified